First report of Phytophthora blight caused by Phytophthora nicotianae on Daphne odora in China - Hu, JiangTao; Zhou, Ying; Luo, SuMei; Zhang, YuanFu; Chen, YuanHua; Cai, Lei; Zhou, YongHui; Li, Rong; Zhang, KaiDong; Liu, ShuYuan; Liu, XiaoPing (Plant disease, 2023)
The variegated leaves and fragrant flowers of Daphne odora var. marginata Mak. make it a popular garden plant. In May 2020, we found diseased D. odora plants in a greenhouse at the Ganzhou Vegetable and Flower Research Institute, in southeast China; 72% of 1800 plants had Phytophthora blight-like symptoms-shrunken stems, black withered branches, wilted and dropped leaves (Fig 1a), and rotted and dark green roots. The root and stem tissue surfaces were disinfected with 75% ethanol for 30 s followed by 0.1% HgCl2 for 1 min, rinsed thrice with sterile water, and cultured on potato-dextrose agar (PDA) medium at 25°C. Mycelia from the diseased tissue were subcultured on fresh PDA medium, providing three colonies. White colonies (~4.1 mm) were formed after 10 days at 25°C (Fig 1b). Sporangia and chlamydospores were induced by placing actively growing mycelia on PDA medium at 25°C for ~30 days and then at 45°C for ~3 days. Sporangia were ovoid to spherical and 19.33 × 20.99 µm in size (Fig 1c), whereas chlamydospores were spherical and 15.68 × 16.10 µm in size (Fig 1d). All three colonies resembled Phytophthora spp. Genomic DNA was extracted from isolates using the Ezup Column Fungi Genomic DNA Purification Kit (Sangon Biotech [Shanghai] Co. Ltd.), and rDNA-ITS and β-tubulin were amplified and sequenced. BLAST analysis (GenBank) revealed that the ITS (Accession No. MZ676071) and β-tubulin (MZ748503) sequences of isolates shared the highest similarity (99-100%) with those of Phytophthora nicotianae (Duccio et al. 2015). A phylogenetic tree of the relationship between our isolate hjt3 and its close relatives within the P. nicotianae species was constructed using the MEGA X neighbor-joining method (Fig 2). The pathogen was identified as P. nicotianae based on morphological and molecular characteristics. Sequencing results of the three samples were consistent, all indicating P. nicotianae. A specimen (JXAU-H2020245) was deposited in the Herbarium of the College of Agronomy, Jiangxi Agricultural University. To confirm pathogenicity, 9-month-old healthy D. odora plants were used for stem and soil inoculation. Stems were cut ~5 cm from the soil with sterilized scalpels and inoculated with 0.8 cm diameter PDA plugs containing actively growing mycelia of isolate hjt3. The soil was sterilized and 0.8 cm PDA plugs containing actively growing mycelia were buried in the soil at ~5 cm; the mycelia were in contact with the roots. Plants in both groups were treated equally; those inoculated with sterile PDA plugs served as controls. There were six plants in each group, with each experiment performed in triplicate. All plants were incubated in a greenhouse at 25-28°C. The stems shrank and began to rot rapidly after 7 days (Fig 3) and the branches turned black and withered within 2 weeks. After soil inoculation, the stems of the inoculated plants blackened and rotted in ~20 days (Fig 4) and the roots rotted and turned dark green (Fig 5). These symptoms rapidly spread to the branches. The control plants did not exhibit any symptoms. Reisolated colonies showed the same morphological traits as the isolates used for inoculation; no target colonies were isolated from the control plants. Phytophthora blight caused by P. nicotianae on D. odora has been reported in Italy (Garibaldi A, 2009) and Korea (Kwon et al. 2005). This is the first detection in China. Therefore, Phytophthora blight on D. odora caused by P. nicotianae should be monitored and controlled to promote the development of the D. odora industry.